NEW APPROACH TO ADDITIONAL LEFT-TURN SECTIONS OF THE TRAFFIC SIGNAL REGULATION - A. P. Zhigadlo; S. V. Dorokhin; D. V. Likhachev (Вестник СибАДИ)
Introduction. The paper describes methods of using the additional left-turn phase of regulation. The authors view the main foreign and domestic methods used in the specialization of the left turn in a separate phase of regulation. To propose a new approach to the specialization of the left-turn direction in a separate phase of regulation the authors investigate one of the most loaded intersections in Voronezh and determine the main characteristics of the traffic flow. Therefore, the authors suggest new parameters in choosing of the necessary method of traffic organization at controlled intersections.Methods and materials. The paper analyses the main methods, which were conditionally related to two approaches: the accident rate of the site and the characteristics of the traffic flow (speed and intensity of the left-turn flow). The authors explained that the new approach, which took into account such parameters as speed, vehicle delays and queue length, allowed effectively controlling the intersection due to the optimal choice of the necessary traffic organization method and due to the result of changes in the parameters by combining the intensity of the left-turn flow and forward flow.Results. The authors developed the approach to the additional left-turn section introduction at the controlled intersection based on a comparison of the left-turn intensity and forward flow and on the analysis of changes in the main characteristics of the traffic flow (speed, vehicle delays and queue length).Discussion and conclusions. The authors concluded that it is necessary to use the proposed approach at the stage of modeling, design and reorganization of the regulated area on the basis of changes in the main characteristics of the traffic flow.